Local DEA app: Saving lives with accessible and well-located automated external defibrillators - Giovanna Natsumi Eiri; Hudson Rogerio Proença Júnior; Miyoko Massago; Vinícius Lopes Giacomin; Karoline Harummy Romero Moriya; Mateus de Amorim Aboboreira; Felipe Hideaki Ueda; Aline Cardoso Machado; Júlia Loverde Gabella; Marcos Rogério Bitencour; Sanderland José Tavares Gurgel; João Ricardo Nickenig Vissoci; et al. (PLoS ONE, 2025)
Purpose Developing technological solutions to reduce care delay and mortality in out-of-hospital cardiac arrest (OHCA) cases is a challenge both in Brazil and worldwide. The aim of this study was to develop and validate a geolocation application for locating automated external defibrillators (AEDs) in the urban area of a medium-sized city in southern Brazil. Methods A mobile application was developed to locate AEDs in public places, indicating the best route to the nearest AED with an intuitive design for emergency use. The app provides information on cardiopulmonary resuscitation (CPR), initial care, and AED use. The research steps included a literature review on the double diamond design process, prototyping, expert validation, and simulation tests. Results The Local DEA app, developed for Android and iOS, offers features such as route calculation to the nearest AED and emergency services. In an evaluation conducted by 30 experts, the app was well accepted for its ease of use and efficiency (Cronbach’s alpha = 0.92). Simulation tests demonstrated that the strategic installation of accessible and well-located AEDs improves coverage and significantly reduces travel time to emergency care as compared with ambulance travel times (p < 0.001). Conclusion The Local DEA app is a promising tool for reducing mortality in OHCA, enabling AED geolocation, use instructions, and CPR guidelines. When combined with the strategic placement of public-access AEDs, the application can increase the likelihood of survival in OHCA cases.